Assessment of Project-Based Learning: Evaluating Its Impact on Students' Writing Proficiency and Academic Outcomes - Hidayati, Dewi (Nexus Publishing NXP, 2023)
Project-based learning (PjBL) has been extensively studied, with numerous theoretical and empirical investigations concluding that it promotes significant growth in students. This study aimed to examine the influence of the PjBL approach and its assessment on students' writing skills in an Academic Writing (AW) course. A pre-experimental design was employed, involving 30 sixth-semester students from STAI Diponegoro Tulungagung, selected through purposive sampling. Pre- and post-tests were used to measure the students' writing skill outcomes. The findings suggest that PjBL can encourage educational practices such as project completion, data presentation, and self-reflection, as well as foster general educational attitudes like teamwork and problem-solving. However, the practical application of driving questions, student-set learning goals, and the use of projects to address essential subjects needs improvement. While scientific procedures were integral to the projects, the extent of student inquiry was unclear. The research indicated that various PjBL components attract the attention of both students and educators. These findings enhance our understanding of PjBL’s potential and the challenges of implementing the proposed assessment in educational settings. The study's insights and the framework of key qualities derived from it can guide research-based implementation and the design of the PjBL approach and related educational areas.